Perspectives of people living with HIV‐1 on implementation of long‐acting cabotegravir plus rilpivirine in US healthcare settings: results from the CUSTOMIZE hybrid III implementation‐effectiveness study. Issue 9 (12th September 2022) - Garris, Cindy P.; Czarnogorski, Maggie; Dalessandro, Marybeth; D'Amico, Ronald; Nwafor, Toyin; Williams, Will; Merrill, Deanna; Wang, YuanYuan; Stassek, Larissa; Wohlfeiler, Michael B.; Sinclair, Gary I.; Mena, Leandro A.; et al.
Abstract: Introduction: The CUSTOMIZE hybrid III implementation‐effectiveness study evaluated implementation of once‐monthly long‐acting (LA) cabotegravir + rilpivirine in diverse US healthcare settings. Here, we report patient participant perspectives after 12 months in CUSTOMIZE. Methods: CUSTOMIZE was a phase IIIb, 12‐month study conducted from July 2019 to October 2020 at eight diverse US HIV clinics that enrolled virologically suppressed people living with HIV‐1 (PLHIV) on a stable oral regimen to receive monthly cabotegravir + rilpivirine LA injections after a 1‐month oral lead‐in. Participants were administered quantitative surveys before injections at months 1 (baseline), 4 and 12. A randomly selected subset of participants was interviewed at baseline and month 12. Data collection at month 12 was completed by October 2020 (during the COVID‐19 pandemic). Results: At baseline, 109 and 34 participants completed surveys and interviews, respectively; 87% were male; 35% were Black or African American. All participants who remained in the study at month 12 ( n = 102) maintained HIV‐1 RNA <50 copies/ml; two participants withdrew due to injection‐related reasons. Mean total scores measuring acceptability and appropriateness of cabotegravir + rilpivirine LA were high at baseline (4.5–4.6 out of 5) and month 12 (4.7–4.9). At month 12, 74% of participants reported nothing interfered with receiving LA injections; injection pain or soreness was the most common concern (15%). Time spent in the clinic and coming to the clinic for monthly injections was very or extremely acceptable after 12 months for most participants (93% and 87%, respectively), with 64% reporting having spent ≤30 minutes in the clinic for injection visits. At month 12, 92% of participants preferred LA injections to daily oral tablets (3%); 97% plan to continue LA treatment going forward. In month 12 interviews, 24 (77%) of 31 participants reported the COVID‐19 pandemic did not impact their ability to receive treatment. Conclusions: Once‐monthly cabotegravir + rilpivirine LA was highly acceptable among PLHIV who were virologically suppressed on a stable antiretroviral regimen and interested in trying LA therapy, with few participants reporting challenges receiving LA injections. Implementation data from CUSTOMIZE suggest that monthly LA injections provide a convenient and appealing treatment option for PLHIV.